Surgical management of necrotizing pancreatitis: An overview - Kokosis, George (World J Gastroenterol, 2014)
Necrotizing pancreatitis is an uncommon yet serious complication of acute pancreatitis with mortality rates reported up to 15% that reach 30% in case of infection. Traditionally open surgical debridement was the only tool in our disposal to manage this serious clinical entity. This approach is however associated with poor outcomes. Management has now shifted away from open surgical debridement to a more conservative management and minimally invasive approaches. Contemporary approach to patients with necrotizing pancreatitis and/or infectious pancreatitis is summarized in the 3Ds: Delay, Drain and Debride. Patients can be managed in the intensive care unit and any intervention should be delayed. Percutaneous drainage can be utilized first and early in the course of the disease, followed by endoscopic drainage or video assisted retroperitoneoscopic drainage if necrosectomy is deemed necessary. Open surgery is now less frequently performed and should be reserved for cases refractory to any other approach. The management of necrotizing pancreatitis therefore requires a multidisciplinary dynamic model of approach rather than being a surgical disease.